Estimating temperatures in a district heating network using smart meter data. (1st October 2022) - Bergsteinsson, Hjörleifur G.; Vetter, Phillip B.; Møller, Jan Kloppenborg; Madsen, Henrik
Abstract: Smart meters at consumers create opportunities to improve operation of the district heating sector using data-driven methods. Information from these meter measurements carries the potential to increase the energy efficiency of both individual houses and the utility network, for example by identifying buildings with too high return temperature, or by detecting leakage in the network. This paper proposes a method for using meter data to estimate network temperatures. Network temperatures can subsequently be used to estimate the network characteristics, namely the nonlinear relationship between network temperature and the plants' temperature and flow. A description of the network characteristics is needed for most temperature-optimisation methods to keep the supply temperature as low as possible without violating the system constraints. Traditionally, measurement wells located in the network have been used. These wells are located at critical points in the network where the largest temperature losses occur. Since the lowest temperature often varies over time, multiple critical points are necessary. The method presented in this paper eliminates the need for these physical critical points in the network. It also makes it possible to change the location of the critical points if needed. The network temperature is estimated using a stochastic state–space model of the heat dynamics from the street level distribution pipe over the service pipe and into individual houses. The parameters in the model are estimated using a maximum likelihood approach, and the Kalman Filter is used to evaluate the likelihood function. The estimation process takes advantage of automatic differentiation using the R package Template Model Builder (TMB ) to reduce the computational workload. The proposed method is validated by comparing the estimated temperature with the temperature measured from a measurement well. Highlights: Estimating network temperature using a group of smart meter data. System of stochastic differential equations of thermodynamics in a pipe is developed. A fast computational method of estimating the likelihood is used for a large system. The presented method creates the possibility for multi-temperature zones.